Analisis Sinkronisasi Hak Asasi Manusia Terhadap Peraturan Daerah - Prabowo, Andrianto; Handayani, Tri Astuti (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
This study aims to explore the extent to which local regulations (Perda) are synchronized with the principles of Human Rights. As an integral part of the national legal system, Perda has an important role in organizing and regulating the lives of local communities. However, there is often a mismatch between local policies and human rights standards, which can lead to discrimination and violations of citizens' basic rights. The research methods used include literature studies, legal analysis, and interviews with legal experts and human rights activists in several selected regions. The results of the study indicate a mismatch between several Perda and human rights principles, which threatens the implementation of fair regional autonomy. Therefore, this study recommends the need for harmonization between Perda and human rights principles to improve human rights protection at the local level. These findings are expected to contribute to the development of legal science and produce more inclusive and fair policies in society